Recurrence of COVID-19: Treading the Fine Line Between Relapse and Re-infection - Ritwick Mondal; Shramana Deb; Durjoy Lahiri; Gourav Shome (University Library System, University of Pittsburgh, 2020)
The ongoing outbreak of COVID-19 that began in Wuhan, China, has constituted a Public Health Emergency of International Concern, with cases confirmed in more than 200 countries. Currently, infected individuals are the primary source of infection and multiple cases of relapse are also reported following the recovery. It is highly concerning the nature of relapse which may be caused due to reactivation or reinfection. While the present testing scenario of using different molecular techniques has several loopholes that can report false results and hamper the process of effectively preventing the transmission of the virus. Various recommendations need modifications to effectively stop the horizontal transmission of the virus and look deeply into the links with relapse cases to prevent a second wave during a pandemic.